2014
DOI: 10.1002/chin.201413261
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Chemistry of 2‐Amino‐3‐cyanopyridines

Abstract: Review: 47 refs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…The preparation of thiazoles was reported in many publications [1][2][3] as they exhibit a significant role in medicinal chemistry [4]. Thiazole derivatives demonstrate good biological spectrum including antibacterial, and antifungal activities [5][6][7][8], in addition to their inhibitory activities of bacterial DNA gyrase B [9]. Numerous thiazole derivatives display promising antibacterial activity via their inhibitory efficacy of the MurB enzyme involved in the biosynthesis of bacterial cell walls [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The preparation of thiazoles was reported in many publications [1][2][3] as they exhibit a significant role in medicinal chemistry [4]. Thiazole derivatives demonstrate good biological spectrum including antibacterial, and antifungal activities [5][6][7][8], in addition to their inhibitory activities of bacterial DNA gyrase B [9]. Numerous thiazole derivatives display promising antibacterial activity via their inhibitory efficacy of the MurB enzyme involved in the biosynthesis of bacterial cell walls [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…From 2‐(2‐cyano‐acetylamino)‐4,5,6,7‐tetrahydro‐benzo[b]thiophene‐3‐carboxamide, Gouda et al reported 4,5,6,7‐tetrahydrobenzothiophene moiety based thiazole and pyrazole derivatives. The derivatives were assessed for antimicrobial activity against Bacillus theringiensis , K. pneumoniae , B. fabe and F. oxysporum by agar diffusion technique in comparison to Ampicillin.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, several publications reported the synthesis of 2‐hydrazineylthiazole derivatives [ 7–9 ] because they exhibit an important role in medicinal chemistry, [ 10 ] such as antibacterial and antifungal agents, [ 11–13 ] as well as inhibitors for bacterial DNA gyrase B. [ 14 ] Several thiazoles exhibit promising antibacterial activities by their inhibition of the MurB enzyme, which is responsible for the biosynthesis of bacterial cell walls.…”
Section: Introductionmentioning
confidence: 99%